DNA metabarcoding reveals the threat of rapidly expanding barred owl populations to native wildlife in western North America. (September 2022) - Kryshak, Nicholas F.; Fountain, Emily D.; Hofstadter, Daniel F.; Dotters, Brian P.; Roberts, Kevin N.; Wood, Connor M.; Kelly, Kevin G.; Schwarcz, Isabel F.; Kulzer, Paige J.; Wray, Amy K.; Kramer, H. Anu; Dumbacher, John P.; et al.
Abstract: Invasive predators can have detrimental impacts on native species and biological communities through direct consumptive effects and indirect effects on trophic interactions, yet these relations are often poorly understood through the initial stages of predator expansion. Leveraging early, lethal collection efforts to study invasive barred owls ( Strix varia ) at the leading edge of their range expansion in northeastern California, we conducted DNA metabarcoding of intestinal samples to assess the diet of this invasive predator. Through the development of customized primers and this novel approach to observing owl diet, we screened the intestinal contents of 124 barred owls and detected a broad diet of 78 unique prey types (48 vertebrates and 30 invertebrates), including prey types undetected in previous methodologies. Mammals were the most consumed vertebrate class (frequency of occurrence = 65 %), followed by amphibians (32 %), birds (22 %), and reptiles (19 %). Diets differed regionally but were similar among ages and sexes and exhibited limited variation in response to local environmental conditions. Our work highlights the generalist predatory strategy of invasive barred owls, identifies numerous native species potentially threatened by their range expansion, and indicates that they will not serve as ecological replacements for congeneric spotted owls ( Strix occidentalis ) they displace. These findings suggest that expanding currently limited barred owl removals could benefit native species and communities in western North America. More broadly, we demonstrate DNA metabarcoding, combined with early intervention, provides a powerful tool for conducting detailed assessments of species consumed by invasive predators, potentially incentivizing conservation actions and improving outcomes. Highlights: We developed custom primers to assess the diet of an invasive predator. We identified 78 unique prey types at a leading edge of an invasion. We demonstrate higher taxonomic resolution than traditional methods. We show how early invasive intervention can aid scientific inquiry. We show that continued barred owl removals may benefit native species.